Determination of capital structure of Malaysian property developers / Fatin Afifah Jajuli - Jajuli, Fatin Afifah (2017)
The purpose of this study is to examine the determinants of capital structure of Malaysian property developers. Cross-sectional regression analysis to establish the moderating effects of the firm-specific variable. The sample includes 30 firms in property sector extracted from Bursa Malaysia, as in 2015 to 2020. The data extracted from BMSB database. In this research, the firm value is measured by its dependent variable which is debt ratio and its independent variable which is profitability, tangibility, growth opportunity, liquidity and non-debt tax shield. The study shows a positive relationship on debt ratio toward profitability and tangibility. However a negative relation between growth opportunity, liquidity and non-debt tax shield. It should be noted that the data comprised only one sector of the Malaysia market which is in the property industry. Thus, the result may differ than the whole Malaysia market. This study contributes to the literature by providing evidence from developing country's perspective.